1997
DOI: 10.1111/j.1442-200x.1997.tb03592.x
|View full text |Cite
|
Sign up to set email alerts
|

A nationwide surveillance study of rheumatic diseases among Japanese children

Abstract: To estimate the number of children with rheumatic diseases, a questionnaire was distributed to the pediatrics department of 1290 hospitals in Japan in June 1994. From this survey, 1606 cases with juvenile rheumatoid arthritis (JRA), 906 cases with systemic lupus erythematosus (SLE), 320 cases with dermatomyositis/polymyositis (DMPM), 28 cases with scleroderma (PSS), 70 cases with Sjogren's syndrome (Sjs), 93 cases with mixed connective tissue disease (MCTD), 25 cases with aortitis syndrome, 20 cases with polya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
1
12

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(55 citation statements)
references
References 2 publications
2
40
1
12
Order By: Relevance
“…More recently, epidemiologic studies from countries other than in Europe and North America showed a different pattern of prevalence of the JIA subtypes as well as a different rate of development of uveitis (a common complication of JIA) (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) as compared with the results obtained in the North American and European studies. A study from Japan showed a very low overall disease prevalence (18), and studies from India and Kuwait showed a much lower than expected rate of antinuclear antibody (ANA) positivity and uveitis (13,17).…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…More recently, epidemiologic studies from countries other than in Europe and North America showed a different pattern of prevalence of the JIA subtypes as well as a different rate of development of uveitis (a common complication of JIA) (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) as compared with the results obtained in the North American and European studies. A study from Japan showed a very low overall disease prevalence (18), and studies from India and Kuwait showed a much lower than expected rate of antinuclear antibody (ANA) positivity and uveitis (13,17).…”
mentioning
confidence: 89%
“…A study from Japan showed a very low overall disease prevalence (18), and studies from India and Kuwait showed a much lower than expected rate of antinuclear antibody (ANA) positivity and uveitis (13,17). Studies of African American patients and black South African patients showed a higher rate of RFpositive polyarticular JIA and a lower rate of uveitis in these ethnic groups (14,19).…”
mentioning
confidence: 99%
“…One survey-based study of 1290 hospitals in Japan determined a crude incidence of 0.01 cases of aortitis per 100 000 children per year. 24 Although comparable data on the incidence of aortitis in Western populations or adults are not available, the epidemiology of the large-vessel vasculitides GCA and Takayasu arteritis, the most common causes of aortitis, has been studied in some depth.…”
Section: Epidemiologymentioning
confidence: 99%
“…100.000 barn på 0,36 (5) og i Finland på 0,37 og 0,9 (6,7). Fra Japan er det rapportert en insidens på 0,47 (8). Den kanadiske studien (5) kan vaere den mest pålitelige fordi alle pasienter som ble innlemmet i aktuelle register hadde på forhånd blitt vurdert og diagnose verifisert av barnerevmatolog (9).…”
Section: Insidensunclassified